The Role of Islamic Religious Education in Shaping a Moderate Character - Auliyaur Rokhim (CV. Agrapana Media, 2025)
This study examines the role of Islamic Religious Education (PAI) in shaping moderate character among students at MI Roudlatul Ulum Bojonegoro. The background of this research stems from the growing need to strengthen religious moderation values in Islamic educational institutions, particularly at the elementary level, as a preventive effort against intolerance and exclusivism. The study aims to analyze how PAI is implemented to internalize moderation values such as justice, tolerance, and balance in students’ daily behavior. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving PAI teachers, students, and school leaders. The findings reveal that the implementation of PAI in the madrasah integrates moderation values through curriculum design, participatory learning strategies, religious habituation, and teacher role modeling. Teachers employ integrative, dialogical, and exemplary methods that emphasize experiential and contextual learning. Furthermore, the school environment, parental support, and community culture serve as strong reinforcing factors, while challenges arise from limited learning resources and external media influences. The study concludes that PAI at MI Roudlatul Ulum effectively cultivates students’ moderate character by harmonizing cognitive understanding, emotional empathy, and moral action. The implication of this research highlights the importance of strengthening teacher training, curriculum innovation, and collaboration among educational stakeholders to sustain Islamic education that promotes peace, inclusivity, and national harmony.